Nanoencapsulation of triterpene 3β, 6β, 16β-trihydroxylup-20(29)-ene from Combretum leprosum as strategy to improve its cytotoxicity against cancer cell lines. Issue 20 (15th October 2020) - Silva-Filho, Carlos J.A.; Freitas, Paulo G.C.; Oliveira, Fátima C.E.; Barbosa, Francisco G.; Oliveira, Maria C.F.; Eloy, Josimar O.; Pessoa, Cláudia; Mafezoli, Jair
Graphical abstract: Highlights: The triterpene was nanoencapsulated with polycaprolactone by nanoprecipitation method. The nanoencapsulation of the triterpene has been analytically confirmed. The nanoencapsulated formula increased cytotoxicity over free form of triterpene. Higher selectivity was found against PC3 and SNB19 tumor cells. Abstract: The pentacyclic triterpene 3β, 6β, 16β-tri-hydroxilup-20(29)-ene is a natural product produced by the Brazilian medicinal plant Combretum leprosum . Its cytotoxicity has been previously reported against breast cancer cell lines. The low water solubility of this natural product, that hampers its bioavailability, motivated the investigation of a new nanoparticle formulation containing the triterpene in order to improve its bioactivity. The triterpene was encapsulated in polycaprolactone (PCL) polymer by nanoprecipitation, producing homogenic nanoparticles with nanometer sizes (122.7 ± 2.06 nm), which were characterized by FT-IR, SEM imaging and DSC. The cytotoxicity (MTT method) of the nanoparticle containing the triterpene 1, besides the free natural product and the nanoparticle control (without 1 ), was assayed against three human tumor cell lines [human colon carcinoma line (HCT116), prostate (PC3) and glioblastoma (SNB19)] and the normal epithelial embryo kidney human cell line (Hek293T). The nanocarrier produced a significative effect in the cytotoxicity of the natural product in the nanoformulation (IC50 0.11–0.26 µg mL −1 ) when compared with its free form (IC50 1.07–1.44 µg mL −1 ). Additionally, higher selectivity of the triterpene to the tumor cells was found when it was encapsulated (SI 1.92–4.54) than in its free form (SI 0.42–0.56). In this case, the nanoencapsulated triterpene was more selective to PC3 (SI 3.33) and SNB19 (SI 4.54) tumor cells.